Hormonal Regulation of the MHC Class I Gene in Thyroid Cells: Role of the Promoter “Tissue-Specific” Region - Giuliani, Cesidio; Verrocchio, Sara; Verginelli, Fabio; Bucci, Ines; Grassadonia, Antonino; Napolitano, Giorgio (Frontiers in Endocrinology, 2021)
IIn previous studies we have demonstrated that the expression of the Major Histocompatibility Complex (MHC) class I gene in thyrocytes is controlled by several hormones, growth factors, and drugs. These substances mainly act on two regions of the MHC class I promoter a “tissue-specific” region (−800 to −676 bp) and a “hormone/cytokines-sensitive” region (−500 to −68 bp). In a previous study, we have shown that the role of the “tissue-specific” region in the MHC class I gene expression is dominant compared to that of the “hormone/cytokines-sensitive” region. In the present report we further investigate the dominant role of the “tissue-specific” region evaluating the effect of thyroid stimulating hormone (TSH), methimazole (MMI), phenylmethimazole (C10), glucose and thymosin-1. By performing experiments of electrophoretic mobility shift assays (EMSAs) we show that TSH, MMI and C10, which inhibit MHC class I expression, act on the “tissue-specific” region increasing the formation of a silencer complex. Glucose and thymosin-1, which stimulate MHC class I expression, act decreasing the formation of this complex. We further show that the silencer complex is formed by two distinct members of the transcription factors families activator protein-1 (AP-1) and nuclear factor-kB (NF-kB), c-jun and p65 respectively. These observations are important in order to understand the regulation of MHC class I gene expression in thyroid cells and its involvement in the development of thyroid autoimmunity.